189 PREVALENCE, DISEASE CHARACTERISTICS AND OUTCOMES OF HEREDITARY TRANSTHYRETIN AMYLOID CARDIOMYOPATHY AMONG ELDERLY INDIVIDUALS. (15th December 2022) - Porcari, Aldostefano; Razvi, Yousuf; Masi, Ambra; Patel, Rishi; Ioannou, Adam; Rauf, Muhammad Umaid; Hutt, David F; Rowczenio, Dorota; Gilbertson, Janet; Martinez-naharro, Ana; Venneri, Lucia; Whelan, Carol; et al.
Abstract: Aims: Transthyretin amyloid cardiomyopathy (ATTR-CM) is often assumed to be associated with wild-type TTR genotype (ATTRwt) in elderly patients (aged ≥70), some of whom are not offered genetic testing. We sought to estimate the prevalence, clinical characteristics and prognostic implications of variant ATTR-CM (ATTRv-CM) among elderly patients. Methods: Data from consecutive patients over 70 years of age diagnosed with ATTR-CM at the UK National Amyloidosis Centre between January 2012 and June 2022 were retrospectively evaluated. All patients underwent clinical evaluation, biochemical tests, echocardiography and TTR genotyping. The study outcome was all-cause mortality. Results: The study population consisted of 2164 patients with ATTR-CM (median age 79 years at diagnosis, 13.2% females, 80.4% Caucasian). ATTRv-CM was diagnosed in 20% (n=431) of the study population of whom 329 (76.3%) carried V122I, 49 (11.4%) T60A, 18 (4.2%) V30M and 35 (8.1%) other pathogenic TTR variants. During a median (range) follow up of 29 (12-48) months, ATTRv-CM was associated with increased all-cause mortality compared to ATTRwt-CM, with the poorest survival observed in V122I-associated ATTRv-CM (p<0.001). Univariable and multivariable binary logistic regression analyses in those with ATTR-CM showed younger age at diagnosis (odds ratio [OR] 0.86 per year, p<0.001), female sex (OR 3.0, p<0.001), Afro-Caribbean ethnicity (OR 59.1, p<0.001), atrial fibrillation (OR 0.65, p=0.015), ischemic heart disease (OR 0.54, p=0.007), peripheral polyneuropathy (OR 3.72, p<0.001) and orthostatic hypotension (OR 3.75, p=0.001) to be independently associated with ATTRv-CM. Conclusions: Up to 20% of elderly patients with ATTR-CM have a pathogenic TTR variant. These findings support routine sequencing of the TTR gene in all patients with ATTR-CM regardless of age.